2017
DOI: 10.1002/jsc.2165
|View full text |Cite
|
Sign up to set email alerts
|

Credit scoring: A historic recurrence in microfinance

Abstract: Microfinance is a new credit segment that can benefit greatly from the advantages the credit scoring technique can offer. In the developing countries even the professionals are not familiar with the technique of credit scoring and many microfinance institutions that serve millions of borrowers do not consider using it. Since the credit scoring technique did not evolve fast enough to meet the needs of microfinance, its adoption by microfinance institutions is slow and resembles more a historic recurrence rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Therefore, mobile payments have gone up. The second major problem of lending to the poor, information asymmetry owing to the unavailability of information on the borrower, was addressed through credit scoring models that bankers have been using for several decades (Bumacov, Ashta, & Singh, 2017). Recently, microfinance institutions have used credit scoring to increase their loan officers' productivity and expand financial inclusion (Bumacov, Ashta, & Singh, 2014).…”
Section: Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, mobile payments have gone up. The second major problem of lending to the poor, information asymmetry owing to the unavailability of information on the borrower, was addressed through credit scoring models that bankers have been using for several decades (Bumacov, Ashta, & Singh, 2017). Recently, microfinance institutions have used credit scoring to increase their loan officers' productivity and expand financial inclusion (Bumacov, Ashta, & Singh, 2014).…”
Section: Opportunitiesmentioning
confidence: 99%
“…Therefore, mobile payments have gone up. The second major problem of lending to the poor, information asymmetry owing to the unavailability of information on the borrower, was addressed through credit scoring models that bankers have been using for several decades (Bumacov, Ashta, & Singh, 2017).…”
Section: Microfinancementioning
confidence: 99%
“…It differs from credit rating which is based on the subjective experience of the evaluators (Bumacov et al, 2014). A credit scoring algorithm contains risk factors and their weights, that is, the relative importance of the risk factor in making the subject a bad credit (Bumacov, Ashta, & Singh, 2017). It has been found that microfinance institutions that use credit scoring can improve performance in terms of growth and efficiency but that it comes at a cost, both for the development of the credit scoring tool and since some good borrowers may be screened out (Bumacov et al, 2014).…”
Section: The Tasks Of Ai In Finance and Financial Marketsmentioning
confidence: 99%
“…Continuous financial innovation requires considering newer technologies, stricter regulation, and increased competition and customers' needs through a participatory approach (Sinha, 2015). Sometimes, an excellent financial performance includes strategies that have a technological component such as mobile banking to increase outreach and reduce costs (Bryson, Atwal, Chaudhuri, & Dave, 2015) or credit scoring to reduce risk (Bumacov, Ashta, & Singh, 2014; Bumacov, Ashta, & Singh, 2017a). Others focus on the social responsibilities of microfinance and either on the social performance or the need to revert to the social mission (Abraham & Kalamkar, 2016).…”
Section: Research Directionsmentioning
confidence: 99%